An analysis of water scarcity in a drought prone city: The case of Ensenada, Baja California, Mexico - Elizondo, Lázaro S.; Mendoza-Espinosa, Leopoldo G. (Tecnología y ciencias del agua, 2020)
The city of Ensenada depends on groundwater, particularly from the Maneadero and Guadalupe aquifer for water supply for agricultural irrigation, urban use, and to support a range of ecosystem functions. Due to intensive extraction, the aquifers' water levels are decreasing and there is water scarcity in the area. Among the solutions implemented by the state of Baja California government is the construction of a desalination plant in Ensenada to meet urban demand, the construction of a new aqueduct to transport water from the Colorado River-Tijuana and the implementation of water reuse for irrigation and aquifer's infiltration. This paper aims to analyze the potential alternatives to mitigate water scarcity in Ensenada region, Baja California, by comparing the costs of water management alternatives and discussing possible solutions. It was found that the use of treated wastewater for irrigation and aquifer's injection could restore aquifers overused at the long term and is more cost-effective from an environmental and economic point of view. Transporting water from Colorado River-Tijuana-aqueduct Ensenada and the construction of a seawater desalination plant are important steps towards provisioning water to Ensenada yet are less desirable due to their environmental impact and the dependency on an already highly impacted watershed.